EFFECT FRAMING DALAM PENGAMBILAN KEPUTUSAN INVESTASI TINJAUAN DARI KEMAMPUAN NUMERIK (STUDI EKSPERIMEN) - Gede Widiadnyana Pasek; I Putu Agus Adnyana; Gde Agung Satria (KRISNA: Kumpulan Riset Akuntansi, 2019)
This paper aims to determine the differences in behavior in investment decision making between those given positive framing and negative framing by looking at good numerical abilities that have high numerical ability and low numerical ability. Conditioning is given to students who are already working. The design of this study uses factorial design that is 2x2, participants are given a case for what investment decisions will be taken, namely continuing investment or not continuing investment because of that the experimental results are analyzed using two-way ANAVA. The results description there were differences in investment decision making between partispann who were given positive framing with participants who were given negative framing and There are differences in investment decision in making between those who have a high numerical level and those who have low numerical abilities. The conclusions drawn from the results of this paper are that giving a framing effect will have an influence on investment decision making as well as numerical ability has differences in investment decision making. Keywords: Framing; Investment Decision; Numerical Ability